The effect of health literacy and self-management efficacy on the health-related quality of life of hypertensive patients in a western rural area of China: a cross-sectional study - Wang, Chenli; Lang, Juntao; Xuan, Lixia; Li, Xuemei; Zhang, Liang (International journal for equity in health, 2017)
Hypertension is a common and frequently occurring chronic disease of the cardiovascular system. Besides the pathological factors, the occurrence and exacerbation of hypertension are also associated with many factors of lifestyle and behaviors. Thus hypertensive patients' Health-related quality of life (HRQL) is not only influenced by the disease itself but also by many subjective factors such as health literacy and self-management efficacy, especially in the deeper part of southwestern China and thus is less developed compared to the other places. The purpose of this study was to examine the association between the HRQL of hypertensive patients and health literacy and self-management efficacy as well as how they affect the HRQL, so as to provide a theoretical reference for improving the HRQL of patients with hypertension in less developed areas. This was a cross-sectional study of baseline data from a clustered randomized controlled trial. The study design had passed a cross-national peer review and accepted grants by the China Medical Board. It was also registered in the Chinese Clinical Trial Registry (ChiCTR-OOR-14005563). A standardized questionnaire adapted from a previous validated WHO questionnaire was used for the survey which included detailed questions about patient's socio-demographic characteristics and self-reported information. Patients' HRQL was measured by the Mandarin version of the 36-item Short Form. We used the validated Mandarin version of the Self-Efficacy for Managing Chronic Disease 6-Item Scale to assess patients' self-management efficacy. The validated three-item Brief Health Literacy Screening (BHLS) was used to measure the patients' health literacy. A structural equation model was constructed, and p ≤ 0.05 was taken as significant. Demographic characteristics, health literacy and self-management efficacy have all significant effects on HRQL. Age, education level, self-management efficacy and health literacy were significantly related to the HRQL. The constructed model had a good fit for the data according to the model fit indices. Based on the model, health literacy (r = 0.604, p = 0.029) and Self-management efficacy (r = 0.714, p = 0.018) have a significant impact on HRQL. Demographic characteristics were inversely related to HRQL (r = -0.419, p = 0.007), but have a significant impact on health literacy (r = 0.675, p = 0.029) and self-management efficacy (r = 0.379, p = 0.029). At the same time, self-management efficacy was positively correlated to health literacy (r = 0.413, p < 0.01). Age, education level, self-management efficacy and health literacy were all related to the HRQL of patient with hypertension, which means that patients who are more elderly and have lower education level, low self-management efficacy and poor health literacy get worse HRQL. This may imply the necessary to introduce routine assessment of health literacy and self-management efficacy into assessment procedures for hypertensive patients' health management. Such assessment can help professionals to identify the population at greatest risk for poor health outcomes and low well-being in the future. In clinical practice, effective interventions such as direct guidance and education to raise the self-management efficacy and enhance health literacy might improve the HRQL of patients with hypertension. Retrospectively registered Chinese Clinical Trial Registry ( ChiCTR-OOR-14005563 ). Name of registry: Effects of the integrated delivery system and payment system of community-based intervention on rural patients of chronic diseases in Qianjiang District, China Date of registration: Retrospectively registered 23 November 2014. Date of enrolment of the first participant to the trial: 5 July 2012.